Optimisation of operating parameters for the removal of ethanol from Zingiber officinale Roscoe (ginger) oleoresin using short-path distillation - Mohamad Samuri, Sazalina (2005)
Due to the importance of exploiting the natural sources to enhance healthier lifestyle, cultivated herbs such as Zingiber Officinale Roscoe or ginger has become our main interest in this research in order to accomplish all the objectives mentioned. Using a statistical software called MINITAB, optimisation on short-path distillation experiments was done and the results showed that feed temperature, along with evaporating temperature and distillate rate were the three operational parameters that influenced the purification process of ginger oleoresin. Feed temperature should be set at 65Â°C and the evaporating temperature also at the same temperature to maximise the oleoresin concentration. The result of the study also point to the advantages and efficiency of feed pre-heating to temperature close or equals to that of evaporating temperature under steady-state conditions for the given operating conditions, prior to its entering the evaporation surface. Although feed rate effect is not statistically significant, it does have linear effect on the oleoresin concentration. The vast difference between theoretical separation efficiency and calculated separation efficiency was probably due to the thickness of liquid film, initial concentration and viscosity of the liquid feed. The theoretical value of recovery yield at feed and evaporating temperature of 65Â°C is 0.99, and experimental value of recovery yield is 0.95. Based on this integrated knowledge on various type of ginger samples, pre-processing methods and more importantly the experience of applying technologies in optimising final purification of ginger oleoresin, would serve to enhance the transfer of advanced technology to local producers.